The Terrorism Trap: The Hidden Impact of America's War on Terror - Akins, John (2019)
Nearly two decades after the declaration of the War on Terror, global terrorist attacks have increased. Beginning in 2005, the levels of domestic terrorism have drastically increased while international terrorism has not. This is a result of U.S. counterterrorism policy shifting towards “disaggregation” in which the U.S. government would focus on breaking up the global al Qaeda network into disconnected groups and rely on partner states’ militaries to target them. In particular, partner states’ focused their counterterrorism operations on the “ungoverned spaces” on their periphery, regions with a history of conflict with the central government and limited government presence in which it was feared al Qaeda and al Qaeda affiliated groups would use as safe havens. Domestic terrorism within partner states rose as a result of revenge attacks from the targeted communities and groups in the periphery in response to the offensive military actions of the state, especially when they resulted in civilian casualties. The increase in domestic terrorism led to further U.S. pressure to expand the counterterrorism operations in the periphery, exacerbating the underlying conditions that led to the outbreak of domestic terrorism. This led partner states to sink deeper into a terrorism trap. This study uses quantitative analysis of a global dataset and case studies of Pakistan, Yemen, Mali, and Egypt to demonstrate and test the terrorism trap theory